(untitled) (Revista de Investigaciones Universidad del Quindío, 2016)
The Gas Electron Multiplier (GEM) is one of the most popular and powerful technologies for gaseous ionization detectors used in high energy physics, medical physics and other applications. One of the fundamental elements of a GEM is foils with micro perforations; the qualities of such perforations are basic for an optimal performance of the GEM. In this work we study different computational methods (implemented in Java programming language), in order to determine the quality of GEM-foils from high resolution images of the foils. This computational method will provide an automatic and high precision alternative to a procedure which, at the moment, is very expensive, slow and imprecise, being a limitation for the development and application of this important technology of detectors.